FIFTY-ONE YEARS OF PATIENCE AS A VIRTUE IN FLORENTINO ARIZA: LOVE IN THE TIME OF CHOLERA - Bülent Cercis TANRITANIR (Fırat University, 2019)
Colombian novelist Gabriel García Márquez, who becomes popular and world wide known with the movement of magic realism and known as Gabo, is regarded as one of the most remarkable names of the twentieth century. In Love in the Time of Cholera Márquez introduces a love story which tries to be ordinary but doesn’t manage to be so. Márquez, in general terms, focuses on theme of love; however, he underlines, in a large extent, patience and waiting. ‘Patience is a virtue’, the sentence survives until today without undergoing changes. Patience, requiring some other virtues such as generoisty, humility, gains different interpretations on human beings. Process of patience, confronting us in Love in the Time of Cholera, revives a different attitude in the minds of the readers. Within this love story, it is possible for each person to find something dealing with himself/herself; however, the most remarkable point about the novel is that waiting lasts for half a century. The objective of the article is to provide us with witnessing the story of Florentino Ariza within a tragic love story in terms when cholera as an epidemic outbreaks. The article approaches his patience as a virtue and reveals his experiences within the process of patience. What Florentio experiences in the half century process of waiting patiently consists the keystones of the article. This article, with its great focus on patience, questions whether Florentino is a patient character or an obsessive lover who just desires to reach his aim.